HIV risks and HIV prevention among female sex workers in two largest urban settings in Croatia, 2008–2014 - Štulhofer, Aleksandar (Array, 2015)
Harm reduction-based HIV prevention has been in place among female sex workers (FSWs) in Croatia for more than a decade. However, little is known about how well the existing programs meet the needs of FSWs in an environment where sex work remains criminalized and highly stigmatized. This study aims to assess changes in FSWs’ vulnerability to HIV infection in the 2008–2014 period. Using convenience samples of FSWs in Croatia’s two largest urban settings, behavioral data were collected in 2007–2008 and 2014. Outreach workers interviewed 154 FSWs in the first wave of the survey and 158 in the second. The period under observation was characterized by a stable prevalence of most HIVrelevant risk behaviors and experiences. Significant changes in client-based victimization and HIV knowledge were observed only among FSWs in the capital city. Substantial and mostly sustained levels of sexual and nonsexual victimization call for more research into the limits of the current behavior-based harm reduction approach to HIV prevention in the country